Evaluation of enzyme immunoassay based on detection of pLDH antigen for the diagnosis of malaria - Vineeta Khare; Priyanka Shukla; Ayesha Ansari; Shadma Yaqoob; Rehana Begum (International Journal of Medical Research and Review, 2016)
Introduction: Timely diagnosis of malaria is a challenge in most endemic areas due to lack of resources. The methods most commonly used are microscopy, regarded as the gold standard, and rapid dipstick tests (RDT) which detect antigens in blood. Enzyme-Linked Immuno Sorbent Assay (ELISA) based tests are fast and easy to perform especially when large number of samples have to be tested. p-LDH is a highly sensitive marker of malaria in blood The present study was done to assess the diagnostic performance of a p-LDH based ELISA on samples from clinically suspected malaria patients.Methods: We tested the sensitivity and specificity of a pLDH based, commercially available ELISA kit on both microscopy positive and negative samples. Microscopy was done for all suspected malaria patients and of these 146 samples (73 positive and 73 negative) were tested by the ErbaLisa PAN (LDH) malaria ELISA kit as well SD Bioline malaria antigen test (RDT) based on detection of both HRP-2 and p-LDH common to all four species.Results: The sensitivity of Elisa was 95.9% while specificity was 93.2 % compared to gold standard microscopy while RDTs had 91.8 % sensitivity and 86.3 % specificity. All 67 samples positive by both microscopy and RDT were also positive by ELISA.Conclusion: p-LDH based ELISA promises to be a cost effective and reliable option for diagnosis of malaria in endemic areas like India.